Asuhan Keperawatan Pendidikan Kesehatan Gizi Seimbang Pada Ibu Bayi A Di Desa Sungai Asam - Romadaningsih, Tri Widya; Santi, Eka (Nerspedia, 2023)
Balanced nutrition is very synonymous with toddlers, because balanced nutrition in toddlers is very important in the growth process. Data from the Karang Intan Health Center 2 of 86 toddlers showed that the distribution of nutrition for toddlers was 1 toddler with poor nutrition, as many as 16 toddlers with malnutrition, as many as 62 toddlers with good nutrition and 7 toddlers with excess nutrition